Kepadatan Sel Hipokampus Insulin Imunoreaktif pada Formasi Hipokampus Mencit yang Diinduksi Berulang dengan Streptozotosin (THE DENSITY OF HIPPOCAMPUS INSULIN IMMUNOREACTIVE CELLS IN HIPPOCAMPUS FORMATION OF REPEAT STREPTOZOSIN INDUCED MICE) - ., Erwin; Pangestiningsih, Tri Wahyu; Widyarini, Sitarina (Jurnal Veteriner; Vol 14 No 2 (2013), 2013)
The presence of insulin in the hippocampus may indicate its involvement in brain cognitive function,such as learning and memory phenomena. The purpose of this study was to find out the density ofhippocampus insulin immunoreactive cells in hippocampus formation in Balb-C mice which treated withstreptozosin repeated as the animal model of diabetes mellitus. Thirty male mice Balb-C strain, aged 12-14 weeks, weight 30-40 g, divided into 2 treatment groups, each group consisted of 15 individuals. GroupI (KI) was treated with sodium citrate buffer, while group II (K2) was treated with streptozotosin at  dose0,5 ml of 40 mg/kg bw in 50 mM sodium citrate buffer pH 4.5 in intra-peritoneal of for five consecutive days.Every two animals from each group euthanasia and necropsied on day 7, 14, 21 and 28 respectively afterthe administration of treatment. Subsequently, the brain tissues were collected and fixatived in NBF10%. Brain sampel were the processed immunohistochemically using anti-insulin mouse antibody. Thedensity of hippocampus insulin immunoreactive cells in hippocampus formation in group 1 were highercompared to group 2. This comparasion as well as the time of observation and interaction between groupand time showed significant differences (p<0.05). it can be concluded that low-dose induction of repeatedstreptozotosin may  cause a decrease in density of hippocampus insulin imunoreaktif cell.
Keywords: streptozotosin, diabetes mellitus, insulin, hippocampus formation, animal model